TRANSFEMINIST SOUNDWALKS: : SHAPING URBAN SPACE THROUGH VOICE AND PRESENCE - Federica Rocchi, Silvia Tagliazucchi and Meike Clarelli (Cadernos IS-UP, 2025)
reflecting on the relationship between the right to the city, the social production of space, and acoustic justice. Confronting the invisibilization and silencing of marginalized bodies in urban public spaces, it introduces the Transfemina – Intersectional Landscapes project and, specifically, Collettivo Amigdala’s methodology for co-creating an urban soundwalk in Modena as a case study. We explore how sound, listening, and walking function as tools for constructing alternative critical cartographies, challenging invisible power relations in public space. The paper argues that these practices foster dynamic alliances among marginalized subjectivities through collective vocal practices, mutual listening, and shared embodied actions. Ultimately, the article posits that these experiences actively constitute an aesthetics of feminist infrastructures—characterized by relationality and resonance—that is intrinsically political and performative. This approach outlines a potent “politics of presence,” not grounded in institutional recognition, but cultivated through embodied encounters, actively shaping and reclaiming urban landscapes.